How People's Motivational System and Situational Motivation Influence Their Risky Financial Choices - Sekścińska, Katarzyna; Maison, Dominika Agnieszka; Trzcińska, Agata (Frontiers in Psychology, 2016)
People’s preferences for risks have been a subject of interest to researchers in both the economy and psychology fields over the last few years. This has given rise to many important findings about the role of psychological factors that influence people’s choices. The presented studies focused on the role of motivational systems (described by Higgins in the Regulatory Focus Theory) in explaining people’s financial choices. The main goal was to examine the relationship between people’s chronic promotion and prevention motivational system and their propensity to (1) invest, (2) undertake investment risks, and (3) assume financial risks in gambling tasks in both the gain and loss decision-making frame. Moreover, we aimed to investigate how chronic motivational systems confronted with situationally induced promotion and prevention motivation would affect people’s propensity to invest and embrace financial risks. Two CAWI studies on a Polish national representative sample (N1 = 1093; N2 = 1096) were conducted. The second study consisted of two waves with a two-week break. The studies provided evidence of higher chronic promotion motivation as well as higher prevention motivation associated with the propensity to invest; however, induced promotion motivation results in a lower propensity to invest compared to induced prevention motivation. Participants with an activated promotion system built more risky portfolios than individuals with an induced prevention system. Moreover, participants with a low chronic promotion system built more risky portfolios than individuals with a high promotion motivation system as long as their prevention system was also low. In terms of gambling decisions in both the gain and loss frame, a higher level of chronic promotion motivation and situationally induced promotion motivation were related to the preference for the non-sure option over the sure one.